2011
DOI: 10.1109/titb.2011.2107746
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of an Instrumental Childbirth for the Training of the Forceps Extraction: Control Algorithm and Evaluation

Abstract: This paper presents the control algorithm implanted on the childbirth simulator BirthSIM in order to provide training to novice obstetricians. The forceps extraction is an obstetric manipulation learned by experience. However, nowadays the training is mainly provided during real childbirths. This kind of training could lead to dramatic consequences due to the lack of experience of some operators. This paper explains the approach that has been used to simulate the dynamic process of a childbirth on the BirthSIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Other studies have also recognized a need for improved training in instrumental delivery techniques [28]. While ‘real-life’ experience is desirable, simulator-based training has been developed and may help fulfill some learning needs [29]. …”
Section: Commentmentioning
confidence: 99%
“…Other studies have also recognized a need for improved training in instrumental delivery techniques [28]. While ‘real-life’ experience is desirable, simulator-based training has been developed and may help fulfill some learning needs [29]. …”
Section: Commentmentioning
confidence: 99%
“…Contrary to electric actuators, pneumatic actuators have however a natural compliance which is highly suitable for a realistic haptic feedback. These cylinders have been sized according to the results from [11] and [12] which showed that the maximal applied force to extract the fetus is about 200N. The stroke of these cylinders have been chosen according to the trajectory extracted from Buttin et al [13] which is similar to the one introduced in Fig.…”
Section: A Designmentioning
confidence: 99%
“…The acquisition of the skills for vacuum application depends on the exposure of junior obstetricians to situations in which they can learn the procedure and train themselves, under the supervision of senior operators [4,5]. The experience of trainees is therefore directly proportional to the number of operative deliveries that take place on patients in the structure where the training takes place.…”
Section: Introductionmentioning
confidence: 99%